An Analysis of Politeness Strategies Used by Male and Female Teachers in EFL Classes in SMP Negeri 4 Kuta Selatan - Dujani, Km. (Universitas Pendidikan Ganesha, 2019)
This study aimed at investigating teachers’ politeness strategies in two teacher’s role which is male and female teacher in EFL classes of the eighth grade students in SMPN 4 Kuta Selatan. The objects of this descriptive qualitative research were utterances delivered by male and female teachers in the classroom activities. This study aimed at finding out (1) describing the types of politeness strategies are used by male English teacher at grade eight of SMPN 4 Kuta Selatan. (2) describing the types of politeness strategies are used by female English teacher (3) explaining the differences in the used of politeness strategies between male and female English teachers. The data were taken from the conversations of the teaching and learning process in the classroom through observation and interviews. The data were gained by observing and video-recording of conversation in classroom discussion and analyzed using politeness strategies by Brown & Levinson (1987). It was found that the differences strategies used by male and female teacher, the male teacher mostly used bald on record has the highest occurrence (175 times) (16.29%) expressions, while the female teacher mostly used positive politeness (257 times) (23.93%) expressions.